2020
DOI: 10.1103/physrevresearch.2.033305
|View full text |Cite
|
Sign up to set email alerts
|

Universal fault-tolerant measurement-based quantum computation

Abstract: Certain physical systems that one might consider for fault-tolerant quantum computing where qubits do not readily interact, for instance photons, are better suited for measurement-based quantum-computational protocols. Here we propose a measurement-based model for universal quantum computation that simulates the braiding and fusion of Majorana modes. To derive our model we develop a general framework that maps any scheme of fault-tolerant quantum computation with stabilizer codes into the measurement-based pic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 108 publications
(213 reference statements)
1
41
0
Order By: Relevance
“…History has shown that the gates a given model is able to achieve is connected with the macroscopic properties of a system, not its microscopic details. Developing our understanding of measurement-based quantum computation in three dimensions by decomposing it in terms of its topological degrees of freedom (16,29) is likely to be a promising route toward better models of two-dimensional fault-tolerant quantum computation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…History has shown that the gates a given model is able to achieve is connected with the macroscopic properties of a system, not its microscopic details. Developing our understanding of measurement-based quantum computation in three dimensions by decomposing it in terms of its topological degrees of freedom (16,29) is likely to be a promising route toward better models of two-dimensional fault-tolerant quantum computation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several constraints the system must satisfy if we realize a controlledcontrolled-phase gate with a two-dimensional system. We first point out that the orientation of boundaries of the topological cluster state is important for the transmission of logical information (29). More precisely, they constrain the temporal directions of the model.…”
Section: Embedding the Non-clifford Gate In Two Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other lattices such as non-foliated lattices [85][86][87] or non-CSS codes [88] can also be considered, including possibly new lattice designs tailored to errors in CV quantum computing.…”
Section: Cluster States and Fault Tolerancementioning
confidence: 99%